2019
DOI: 10.1002/hlca.201900023
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Total Synthesis of (−)‐Doliculide Using Catalytic Asymmetric Hydrogenations

Abstract: A concise and efficient strategy has been developed to construct a polyketide chain by employing relay asymmetric hydrogenations catalyzed by two chiral spiro iridium catalysts. By using this strategy, an enantioselective total synthesis of (−)‐doliculide has been achieved in 19 steps with 6.9 % overall yield. The route features high enantioselectivity and diastereoselectivity. The catalyst loading can be as low as 0.005 mol‐%. It is convenient to obtain natural polyketides and their analogues by this strategy. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Indeed, under the conditions using BOPCl for activation the doliculide precursors could be obtained in good yields. [29] To our surprise, while measuring the NMR spectra in non-stabilized CDCl 3 , doliculide was chlorinated at the tyrosine moiety to the derivative 17 d.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, under the conditions using BOPCl for activation the doliculide precursors could be obtained in good yields. [29] To our surprise, while measuring the NMR spectra in non-stabilized CDCl 3 , doliculide was chlorinated at the tyrosine moiety to the derivative 17 d.…”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al reported a synthetic route using asymmetric hydrogenations to introduce the stereogenic centers in the polyketide chain. [29] Very recently Yadar et al reported an approach based on asymmetric Evans alkylations and Sharpless epoxidations. [30]…”
Section: Introductionmentioning
confidence: 99%
“…Commercially-available 10 was hydrogenated at 100 atm using (S a )-Ir-spiroSAP or (R a )-Ir-spiroSAP as the catalyst to give enantiomers 11a or 11b, respectively. 31,32 11a and 11b were hydrolyzed by heating overnight in a solution of 5 M NaOH to generate 4a and 4b. Protection and extension of 4a and 4b into 6a and 6b were performed as in the chemoenzymatic route.…”
Section: Stereoselectivitiesmentioning
confidence: 99%
“…12a was reduced using (S a )-Ir-spiroSAP or (R a )-Ir-spiroSAP and hydrolyzed to provide 9aa or 9ab, (77% and 97% yields, respectively, through two steps). 31,32 Likewise, 12b was reduced using (S a )-Ir-spiroSAP or (R a )-Ir-spiroSAP and hydrolyzed to provide 9ba or 9bb (83% and 86% yields, respectively, through two steps). Coupling with NAC yielded 8aa, 8ab, 8ba, and 8bb.…”
Section: Stereoselectivitiesmentioning
confidence: 99%